2023
DOI: 10.1007/s11628-023-00527-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived value of AI-based recommendations service: the case of voice assistants

Abstract: The application of artificial intelligence in services is continuously spreading. In particular, one of the most important recent trends is the development of virtual assistants, more particularly; voice assistants, which provide consumers with various services (e.g. information, music) and with product and service recommendations based on their preferences. There is a need to understand how valuable these recommendations are for consumers. This study contributes to the emerging body of research into consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 98 publications
(175 reference statements)
1
8
0
Order By: Relevance
“…For instance, Chen et al (2021) studied the use of AI chatbots (used by establishments to avail of 24-hour customer relationship management services) in the banking sector and discovered that clients regarded chatbot interactions to be convenient and effective, which increased customer satisfaction. Similar to this, a study on the use of virtual assistants powered by AI in customer service showed that customers valued rapid, tailored support, which led to higher satisfaction (Akdim & Casaló, 2023).…”
Section: Empirical Review Of Literaturesupporting
confidence: 58%
See 1 more Smart Citation
“…For instance, Chen et al (2021) studied the use of AI chatbots (used by establishments to avail of 24-hour customer relationship management services) in the banking sector and discovered that clients regarded chatbot interactions to be convenient and effective, which increased customer satisfaction. Similar to this, a study on the use of virtual assistants powered by AI in customer service showed that customers valued rapid, tailored support, which led to higher satisfaction (Akdim & Casaló, 2023).…”
Section: Empirical Review Of Literaturesupporting
confidence: 58%
“…Most of the common AI applications include knowledge-based expert systems, but other AI technologies like neural networks and speech syntheses are also much in use. However, managers and developers lack an understanding of practical issues affecting AI, management, and organizations (Buła & Niedzielski, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, this study explored text‐based chatbots, and voice‐based chatbots (e.g., Siri and Alexa) have been used in the online customer service industry as intelligent assistants (Akdim & Casaló, 2023; Aw et al, 2022). Future research could use voice‐based chatbots as research subjects to explore the differences between them and humans.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…Conversational and virtual agents, commercial chatbots and robo-advisors guiding financial investments are examples of this shift to more user-oriented technology-led service encounters. In this Special Issue Camilleri and Troise (2023) investigate how chatbots mimic human customer services' abilities, and Akdim and Casaló (2023) analyze the customers' value and engagement in relation to these voice assistants.…”
Section: Living In a Technology-led Environmentmentioning
confidence: 99%